Analysis of Dominant Physical Conditions of Futsal Academy Players in Semarang City - Firmansyah, Ilham; Anam, Khoiril (Fair Play, 2025)
The purpose of this research is to find out the dominant physique in futsal academy players in Semarang city. The target of this research is futsal academy players in Semarang City. This study is a quantitative descriptive. The independent variable is the Semarang City Futsal Academy. The population consists of futsal players from the Semarang Academy. The sampling technique used in this study is purposive sampling. The results showed the following Leg muscle strength had an average score of 48.39, with all (100%) athletes categorized as very poor. Agility had an average score of 18.45, with all (100%) athletes categorized as very poor. good. Endurance had an average score of 45.47, with all (100%) athletes categorized as good. Based on the above findings, it can be concluded that the dominant physical conditions of futsal academy players in Semarang City, as analyzed through a physical condition survey, generally fall into the moderate category.